Corporate finance workbook a practical approach - Clayman, Michelle R.; Fridson, Martin S.; Troughton, George H. (CFA Institute investment series., 2012)
"The book that fills the practitioner need for a distillation of the most important tools and concepts of corporate financeIn today's competitive business environment, companies must find innovative ways to enable rapid and sustainable growth not just to survive, but to thrive. Corporate Finance: A Practical Approach is designed to help financial analysts, executives, and investors achieve this goal with a practice-oriented distillation of the most important tools and concepts of corporate finance.Updated for a post-financial crisis environment, the Second Edition provides coverage of the most important issues surrounding modern corporate finance for the new global economy: Preserves the hallmark conciseness of the first edition while offering expanded coverage of key topics including dividend policy, share repurchases, and capital structure Current, real-world examples are integrated throughout the book to provide the reader with a concrete understanding of critical business growth concepts Explanations and examples are rigorous and global, but make minimal use of mathematics Each chapter presents learning objectives which highlight key material, helping the reader glean the most effective business advice possible Written by the experts at CFA Institute, the world's largest association of professional investment managers Created for current and aspiring financial professionals and investors alike, Corporate Finance focuses on the knowledge, skills, and abilities necessary to succeed in today's global corporate world"--